2020
DOI: 10.1001/jamaoncol.2020.3161
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vocimagene Amiretrorepvec in Combination With Flucytosine vs Standard of Care on Survival Following Tumor Resection in Patients With Recurrent High-Grade Glioma

Abstract: IMPORTANCE New treatments are needed to improve the prognosis of patients with recurrent high-grade glioma.OBJECTIVE To compare overall survival for patients receiving tumor resection followed by vocimagene amiretrorepvec (Toca 511) with flucytosine (Toca FC) vs standard of care (SOC). DESIGN, SETTING, AND PARTICIPANTSA randomized, open-label phase 2/3 trial (TOCA 5) in 58 centers in the US, Canada, Israel, and South Korea, comparing posttumor resection treatment with Toca 511 followed by Toca FC vs a defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 21 publications
0
81
0
3
Order By: Relevance
“…Despite recent advances in the treatment of malignant glioma, prognosis remains poor with a median overall survival (OS) of less than two years in IDH-wildtype glioblastomas [ 1 , 2 ]. Upon inevitable tumor recurrence, median post-recurrence survival (PRS) is limited to 7–12 months in most recent studies [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Salvage treatment options include resurgery, reirradiation protocols, chemotherapy and any combination thereof.…”
Section: Introductionmentioning
confidence: 99%
“…Despite recent advances in the treatment of malignant glioma, prognosis remains poor with a median overall survival (OS) of less than two years in IDH-wildtype glioblastomas [ 1 , 2 ]. Upon inevitable tumor recurrence, median post-recurrence survival (PRS) is limited to 7–12 months in most recent studies [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Salvage treatment options include resurgery, reirradiation protocols, chemotherapy and any combination thereof.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the 5-year survival rate is only approximately 5% (Stupp et al, 2009;Ostrom et al, 2017). Due to the high cost of treatment of glioblastoma and poor treatment effect, it has always been one of the difficulties in tumor treatment (Cloughesy et al, 2020;Faria et al, 2020;Reardon et al, 2020). Therefore, it is of great importance to find effective molecular targets and improve the prognosis of glioblastoma.…”
Section: Introductionmentioning
confidence: 99%
“…Vocimagene amiretrorepvec (Toca 511) or Toca 511 with flucytosine (Toca FC) have been evaluated in Phase I clinical trials which demonstrated safety and good tolerability, with tumor regression at the site of infusion and durable responses in patients with recurrent high-grade glioma (Cloughesy et al, 2018 ). However, a recent phase III clinical trial (NCT02414165) revealed that among 403 randomized patients who underwent tumor resection for first or second recurrence of GBM or anaplastic astrocytoma, administration of Toca511 or Toca FC compared with standard of care did not improve overall survival or other efficacy end points (Cloughesy et al, 2020 ).…”
Section: Approaches To Gene Therapymentioning
confidence: 99%